EL COMERCIO DEL AGUA VIRTUAL. GOTA A GOTA EL AGUA SE AGOTA… (cartel colocado en lo alto de la Tribuna Norte del Estadio Nacional) - Domingo Begazo, José (2009)
Water and oil are two products that will be depleted in this century. Ernesto Sabato and Alvin Toffler suggested that future wars will be wars over watersheds. Peru has signed an FTA with the U.S. and is expected to sign with China, Korea and other countries, economically more powerful; they buy organic foods and products they require, but that in turn to Peru will cause the loss of their water footprint. Anyone who has walked through the Plaza de Armas of Quito find on the front of the cathedral a large bronze plaque which indicates that there came the expedition to find the Amazonas river, which led them a long time the idea that they were a country Amazon or right to use the waters of that river. I must admit that the government of Alberto Fujimori made a big role in cutting the expansionist idea..